The effectiveness of pulmonary tuberculosis screening system in reducing diagnosis delay In Khok Samrong hospital, Lopburi province - Wattanatorn , Supaporn; Phukwapee , Daranee (Journal of Medical and Public Health Region 4, 2020)
This study aims to determine the effectiveness of new pulmonary tuberculosis (PTB) screening system in reducing diagnosis delay In Khok Samrong hospital, Lopburi province. Medical records of new PTB cases (TB01 and TB03) registered for treatment in the hospital following the new PTB screening system during 15 June 2015 to 15 December 2015. The new program included symptom screening for suspected PTB at the hospital visit check point, separating the suspected PTB with mask provision, and then further screening for PTB. Persons 18-60 years with symptoms suspected of PTB received chest X-ray while all the elderly > 60 years received chest X-ray. Persons with abnormal chest X-ray had sputum direct smear for acid fast bacilli (AFB). These data were compared with those of new PTB cases during 15 June 2014 to 15 December 2014, the same period of the year before launching the new screening program. Descriptive statistics included frequency, percentage, mean and standard deviation. Unpaired t-test and chi-square test were used for comparison between means and proportions respectively. The study found that the duration between first hospital visit and PTB diagnosis by the new screening system (2.34 days) was significantly (p < 0.001) lower than that by the previous traditional screening system (7.63 days). The severity of PTB by the new screening system was significantly (p = 0.03) less than the traditional screening. The satisfaction of the new screening system among the TB health care personnel was reported 100%. This screening might help in early detection of PTB case findings and increase target coverage.